CircN4bp1 Facilitates Sepsis-Induced Acute Respiratory Distress Syndrome through Mediating Macrophage Polarization via the miR-138-5p/EZH2 Axis. (30th December 2021) - Zhao, Dongyang; Wang, Chunxue; Liu, Xiandong; Liu, Na; Zhuang, Shougang; Zhang, Qianqian; Bao, Xiaowei; Xu, Shumin; Zhou, Xiaohui; Meng, Qinshu; Li, Shao; Tang, Lunxian
Abstract : We recently reported the differential circRNA expression patterns of the pulmonary macrophages in sepsis-induced acute respiratory distress syndrome (ARDS) mice model by microarray analysis. However, their function and hidden molecular mechanism in regulation of macrophage activation and inflammation remain poorly understood. In this study, we found that circN4bp1was overexpressed in PBMC and monocytes, and its expression levels were correlated with a poor prognosis in sepsis induced ARDS patients induced by sepsis. Knockdown of circN4bp1 inhibited the lung injury and improved the long-time survival through blunting the M1 macrophage activation in cecal ligation and puncture- (CLP-) induced ARDS mice. Moreover, bioinformatics analysis predicated a circN4bp1/miR-138-5p ceRNA network, which was confirmed by luciferase reporter assay and RNA binding protein immunoprecipitation (RIP). CircN4bp1 affected macrophage differentiation by binding to miR-138-5p, thus regulating the expression of EZH2 in vivo and ex vivo. Lastly, the m6A level of circN4bp1was found to be elevated in ARDS mice; inhibition of m6A methyltransferase METTL3 blocked this response in vitro. Therefore, circN4bp1 can function as a miR-138-5p sponge for the modulation of macrophage polarization through regulation the expression of EZH2 and may serve as a potential target and/or prognostic marker for ARDS patients following sepsis.